Lithological Structure and Oil and Gas Source Potential of the Chernoyarsk Horizon in the Central Part of the Rubezhinsky Trough (Based on Drilling Results) - V. A. Rybakova; A. P. Vilesov; V. A. Kozlova; N. Yu. Grebenkina; V. S. Ledenev; D. V. Solodov (Georesursy, 2025)
The Chernoyarsk horizon of the Middle Devonian is one of the most poorly studied source rock in the south of the orenburg region. The data obtained from the results of drilling the first exploratory well on the territory of the Solnechnyj License area (LA) in the Rubezhinsky trough (southern part of theBuzuluk depression) allowed us to obtain new information about the facies genesis and material composition of the rocks of the Chernoyarsk horizon, clarify their oil and gas production potential and update the concepts of the formation of the oil and gas potential of the region. Sedimentation in the lower part of the Chernoyarsk horizon occurred in conditions of a relatively deep sublittoral (below the wave basis), and in the upper part – in conditions of prodelta. In the rocks of the horizon, signs of bottom anoxia are observed – micro-bedding, abundance of planktonic and nectonic fossil of good preservation, rarity of bioturbation, abundant pyritization by organics. Integration of lithological and geochemical studies has confirmed the good generation potential of the oil and gas sorce rock of the Chernoyarsk horizon. The type of organic matter is defined as sapropelic (type II), the pyrolyticparameter Tmax 448–459 ºC, which corresponds to the end of the oil window and the beginning of condensate/fatty gas generation. The values of total organic carbon (TOC) are ~ 2 % (rarely up to 5 %), which indicates a high degree of maturity and depletion of organic matter.